Praxis pietatis, avagy a kegyesség gyakorlata. Hit és cselekedet kapcsolata az Újszövetségben – egy hatástörténeti csomópontból nézve - HANULA, Gergely (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2023)
Praxis Pietatis, or the Practice of Piety: The Relationship between Faith and Deeds in the New Testament ─ From the Perspective of a Historical Impact Point This article delves into the intricate relationship between faith and deeds as it pertains to the teachings of the New Testament, drawing from the legacy of the Reformation. It emphasizes the necessity of re-evaluating church doctrine based on the foundation of the Scripture. However, it recognizes that understanding the message of the Scripture is not an objective, detached process but rather one that is deeply entwined with individual religious experiences and interpretations. The dynamic interaction between faith and the tangible, visible world shapes our comprehension of the Bible’s words and meanings. The complex interplay of faith and deeds is recognized, as various denominations stress different aspects of biblical teachings. The role of faith in the New Testament is not solely to lead to salvation; it also establishes a framework for the believer’s relationship with good deeds, setting it within a temporal framework. The New Testament understanding of salvation, whether it is eternal life or the acquisition of God’s kingdom, is framed by the faith of God’s chosen people, and this faith presupposes the intervention of God. Thus, faith cannot be separated from God’s action, making it the foundation for understanding good deeds.